Whiteness and School Shootings: Theorization toward a More Critical School Social Work. Issue 3 (21st August 2020) - Gregory, Joshua R
Abstract: In the United States, school shootings have become an increasingly prevalent and publicly salient social problem. School social workers play a central role in developing understanding of their etiology and intervening to prevent their further occurrence. Even though nearly all school shootings are committed by white students, no etiological theory has contemplated the possibility that whiteness contributes in any meaningful way to the perpetration of school shootings. Popular theories suggest that gun availability, mental illness, and bullying bear some relationship to school shootings; however, levels of gun availability, mental illness prevalence, and bullying victimization do not differ substantially between whites and non-whites, indicating that these factors might account for school shootings within, but not between, races. The present article takes up the task of beginning to theorize the relationship between whiteness and school shootings, exploring the likelihood that whiteness acts as a moderator, leading whites, but not non-whites, to commit school shootings in response to similar antecedents. This novel theorization provides an opening for school social workers to more critically interrogate whiteness not as an individual trait, but as a structural phenomenon that influences not only the etiology of school shootings, but schools and educational processes more broadly.